2006
DOI: 10.1177/0894318406289878
|View full text |Cite
|
Sign up to set email alerts
|

Research-Based Theatre: The Making of I’m Still Here!

Abstract: This column describes the process undertaken by a team of researchers, artists, and actors to create a research-based drama about living with dementia. Researchers had several studies, guided by the human becoming theory, about what life was like when living with dementia, and an additional study in progress about the lived experience of loss for daughters whose mothers were diagnosed with Alzheimer's disease. Researchers partnered with an experienced artistic director and playwright in order to craft a script… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 4 publications
0
72
2
Order By: Relevance
“…Initially used in research for representation and dissemination of findings, arts-based methods are now employed in all stages of inquiry (Fraser & Sayah, 2011): as a stimulus for data generation, a method for eliciting meanings and values, an intervention tool or a form of dissemination (Bergum & Godkin, 2008). A wide range of artistic forms are utilized by Canadian arts-based researchers: dance (Boydell et al, 2011); poetry (Groft & Robinson-Vollman, 2007;Lapum, 2005); theatrical performances (Cox et al, 2009a;Colantino et al, 2008;McIntyre & Cole, 2008;Clarke & Nisker, 2007;Doucet et al, 2007;Kontos & Naglie, 2007;Eakin & Endicott, 2006;Mitchell et al, 2006;Nisker et al, 2006;Sinding et al, 2006;Gray et al, 2000;; visuals (Poudrier & MacLean, 2009, Castleden & Garvin, 2008Oliffe & Botorff, 2007;Moffitt & Robinson-Vollman, 2004); and a combination of various forms of art (Cox et al, 2009b;.…”
Section: Introductionmentioning
confidence: 99%
“…Initially used in research for representation and dissemination of findings, arts-based methods are now employed in all stages of inquiry (Fraser & Sayah, 2011): as a stimulus for data generation, a method for eliciting meanings and values, an intervention tool or a form of dissemination (Bergum & Godkin, 2008). A wide range of artistic forms are utilized by Canadian arts-based researchers: dance (Boydell et al, 2011); poetry (Groft & Robinson-Vollman, 2007;Lapum, 2005); theatrical performances (Cox et al, 2009a;Colantino et al, 2008;McIntyre & Cole, 2008;Clarke & Nisker, 2007;Doucet et al, 2007;Kontos & Naglie, 2007;Eakin & Endicott, 2006;Mitchell et al, 2006;Nisker et al, 2006;Sinding et al, 2006;Gray et al, 2000;; visuals (Poudrier & MacLean, 2009, Castleden & Garvin, 2008Oliffe & Botorff, 2007;Moffitt & Robinson-Vollman, 2004); and a combination of various forms of art (Cox et al, 2009b;.…”
Section: Introductionmentioning
confidence: 99%
“…people with dementia) in more positive ways (Mitchell et al, 2006;Kontos & Naglie, 2007); can provoke and facilitate memory and reminiscence processes (Boggs & Leptak, 1991); can be a useful way of learning about and/or introducing sensitive topics (e.g. finances or widowhood) (Ritch & Brennan, 2010;Feldman et al, 2011); and can be an effective educational tool with practitioners (Kontos & Naglie, 2007).…”
Section: Devised Productions (N=9)mentioning
confidence: 99%
“…In their systematic review of the literature, Fraser and al Sayah (2011) identified that the integration of arts within health research (both as a form of knowledge production and knowledge translation) emerged with increased qualitative inquiry within the health sciences, particularly the use of theatre as a frequent arts-based dissemination strategy. As an engaging pedagogical tool (Price et al, 2007), the use of arts and theatre is suggested to be more effective than conventional teaching methods for enhancing practitioner skills for complex physical Mitchell, Jonas-Simpson, & Ivonoffski, 2006) and social health-related conditions (Eakin & Endicott, 2006;Rossiter et al, 2008). Theatrical productions based on qualitative research findings are grounded in real life scenarios, encompassing verbatim quotes and embodying recurrent themes that represent a personified and vital piece that health care professionals can empathize with (Gray, Fitch, Labrecque, & Greenberg, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include "Ed's Story" and the Pulitzer Prize-winning play "Wit, " which also won the 2002 National Innovations in Medical Education Award (Deloney & Graham, 2003;Lorenz, Steckart, & Rosenfeld, 2004). Theatre has also been used to educate health professionals about such conditions including traumatic brain injury , dementia (Kontos & Naglie, 2007;Mitchell et al, 2006), cancers (Gray et al, 2003;Gray et al, 2000) and AIDS (Shapiro & Hunt, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation